2023
DOI: 10.3390/hydrology10070136
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Fuzzy Analytic Hierarchy Process (F-AHP) and Fuzzy Logic for Flood Exposure Risk Assessment in Arid Regions

Abstract: Flood risk assessment is an important tool for urban planning, land development, and hydrological analysis. The flood risks are very high in arid countries due to the nature of the rainfall resulting from thunderstorms and the land cover, which comprises mostly very dry arid soil. Several methods have been used to assess the flood risk, depending on various factors that affect the likelihood of occurrence. However, the selection of these factors and the weight assigned to them remain rather arbitrary. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It is a multicriteria method commonly used for qualitative and quantitative analysis of a hierarchical list of the most influencing factors to get insights on the decisionmaking process. The presence of fuzziness and vagueness in many decision-making scenarios often leads to imprecise judgments in conventional AHP approaches [31]. Consequently, several researchers (e.g., [30,32,33]) have focused on studying fuzzy AHP, an extension of Saaty's theory, and have indicated that fuzzy AHP offers a more comprehensive description of the analyzed process than the traditional AHP method (Table 4).…”
Section: Fuzzy Analytical Hierarchy Process (F-ahp)mentioning
confidence: 99%
“…It is a multicriteria method commonly used for qualitative and quantitative analysis of a hierarchical list of the most influencing factors to get insights on the decisionmaking process. The presence of fuzziness and vagueness in many decision-making scenarios often leads to imprecise judgments in conventional AHP approaches [31]. Consequently, several researchers (e.g., [30,32,33]) have focused on studying fuzzy AHP, an extension of Saaty's theory, and have indicated that fuzzy AHP offers a more comprehensive description of the analyzed process than the traditional AHP method (Table 4).…”
Section: Fuzzy Analytical Hierarchy Process (F-ahp)mentioning
confidence: 99%
“…In recent times, the use of artificial intelligence (AI) and machine learning (ML) has shown potential in enhancing the precision and efficiency of modeling changes in water supplies via the analysis of GRACE satellite data [3,[26][27][28][29]. Different models have been employed, including ANN, fuzzy logic, and hybrid learning [30]. The use of AI-based methods to model GRACE TWS has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Gaussian membership functions have been used in research to overcome problems with basic triangular and trapezoidal membership functions [46,47]. However, research [48] has found that, on observed data, fuzzy logic system results are more conservative than those of Fuzzy AHP and the equal weights method. This could suggest that the classical fuzzy system is more appropriate for risk assessment.…”
Section: Introductionmentioning
confidence: 99%